Neurological Involvement in Primary Systemic Vasculitis - Zhang, Shanshan; Yuan, Dongli; Tan, Ge (Frontiers in Neurology, 2019)
Primary systemic vasculitis can affect every structure in both the central and peripheral nervous system, causing varied neurological manifestations of neurological dysfunction. Early recognition of the underlying causes of the neurological symptoms can facilitate timely treatment and improve the prognosis. This review highlights the clinical manifestations of primary systemic vasculitis in the nervous system.